2017
DOI: 10.5194/acp-17-9717-2017
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of riming: the retention of organic and inorganic atmospheric trace constituents

Abstract: Abstract. During free fall in clouds, ice hydrometeors such as snowflakes and ice particles grow effectively by riming, i.e., the accretion of supercooled droplets. Volatile atmospheric trace constituents dissolved in the supercooled droplets may remain in ice during freezing or may be released back to the gas phase. This process is quantified by retention coefficients. Once in the ice phase the trace constituents may be vertically redistributed by scavenging and subsequent precipitation or by evaporation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 68 publications
4
18
1
Order By: Relevance
“…Using the CH 2 O SE calculated by Fried et al () using the n‐butane ratio method (67 ± 20%), to avoid potential errors from using a horizontally averaged background profile in the altitude‐dependent calculation, we still find r f <0.25 for CH 2 O. These results conflict with the laboratory measurements of r f =0.97 for CH 2 O (Jost et al, ). Nevertheless, for the severe storm and MCS, the analysis in the previous section indicates that the simulations are overestimating precipitation production, and thus, the true r f values may be higher.…”
Section: Ice Retention Fractions Determined Using Simulations and Obscontrasting
confidence: 77%
See 3 more Smart Citations
“…Using the CH 2 O SE calculated by Fried et al () using the n‐butane ratio method (67 ± 20%), to avoid potential errors from using a horizontally averaged background profile in the altitude‐dependent calculation, we still find r f <0.25 for CH 2 O. These results conflict with the laboratory measurements of r f =0.97 for CH 2 O (Jost et al, ). Nevertheless, for the severe storm and MCS, the analysis in the previous section indicates that the simulations are overestimating precipitation production, and thus, the true r f values may be higher.…”
Section: Ice Retention Fractions Determined Using Simulations and Obscontrasting
confidence: 77%
“…Retention fractions for hydrometeor surfaces with temperatures above freezing (wet growth riming) are likely lower (e.g., r f (i l) < 0.2, where r f (i l) refers to the fraction remaining in the ice core to that in the liquid (Michael & Stuart, )) than for below freezing hydrometeor surfaces (dry growth riming) because in wet growth riming, species are preferentially expelled from the frozen portion of the hydrometeor interior into the quasi‐liquid surface layer. Dry growth riming ice retention fractions have been measured in laboratory and field experiments (e.g., r f =0.05–1.0 for H 2 O 2 , Jost et al, ; Iribarne & Pyshnov, ; Snider et al, ; Snider & Huang, ; Voisin et al, ; von Blohn et al, , ). Ice retention of species that dissociate or react in cloud water can be affected by the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, HNO 3 is completely retained (Iribarne & Pyshnov, ; von Blohn et al, ), while the observed retention fraction is 0.62 for SO 2 (Iribarne et al, ), which is less soluble than HNO 3 . Jost et al () measured the retention coefficients of formaldehyde by wind tunnel experiments. The retention coefficients they obtained for CH 2 O were 0.97 ± 0.11 and did not depend significantly on temperature or ventilation.…”
Section: Introductionmentioning
confidence: 99%